2011
DOI: 10.1038/ejhg.2010.205
|View full text |Cite
|
Sign up to set email alerts
|

Consanguinity around the world: what do the genomic data of the HGDP-CEPH diversity panel tell us?

Abstract: Inbreeding coefficients and consanguineous mating types are usually inferred from population surveys or pedigree studies.Here, we present a method to estimate them from dense genome-wide single-nucleotide polymorphism genotypes and apply it to 940 unrelated individuals from the Human Genome Diversity Panel (HGDP-CEPH). Inbreeding is observed in almost all populations of the panel, and the highest inbreeding levels and frequencies of inbred individuals are found in populations of the Middle East, Central South … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 27 publications
(26 reference statements)
7
55
0
Order By: Relevance
“…This allowed us to obtain a more accurate estimation of the level of inbreeding in the Lebanese population. 6 In previous studies, F was estimated using Malécot's formula applied to sociological data from first cousin unions. Based on the assumption that 25% of marriages occur between first cousins, F was found to be equal to 1.56%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allowed us to obtain a more accurate estimation of the level of inbreeding in the Lebanese population. 6 In previous studies, F was estimated using Malécot's formula applied to sociological data from first cousin unions. Based on the assumption that 25% of marriages occur between first cousins, F was found to be equal to 1.56%.…”
Section: Discussionmentioning
confidence: 99%
“…3,[7][8][9] Using biological methodologies, an F estimation was first calculated using a microsatellite panel and FEstim algorithm and was then improved using genome-wide single-nucleotide polymorphism (SNP) chip-based advanced algorithms. 5,6 These estimations were based on the genotyping of a large number of genetic markers to infer the individual genomic proportion that is homozygous by descent (HBD). Two parameters were then calculated; the proportion of genomic HBD and the average length of the HBD segments, which are the indicators of the inbreeding and the age of common ancestors, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The geographic location of genetic isolates in Argentina in the clusters with high random consanguinity highlights the usefulness of this approach in identifying isolates with reduced genetic heterogeneity and reduced effective population size. Since the occurrence of rare Mendelian diseases is common in some isolates, their identification, such as selection of candidate populations to be molecularly studied is made (Leutenegger et al 2011), also has great health care relevance.…”
Section: Discussionmentioning
confidence: 99%
“…consang.net). More recently, relying on genomic data, Leutenegger et al (2011) estimated the inbreeding levels and mating-type proportions in 52 populations from all continents. They found that consanguinity was present in almost all populations with the highest rates of inbreeding in North Africa, the Middle East, and Central South Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, evidence for inbreeding was established within a subset of the HGDP-CEPH panel. 11 A variety of methods are available to determine relatedness between individuals based on genotype data. We adopted three complementary approaches.…”
Section: And Monks Et Al 9 )mentioning
confidence: 99%